Applying an Islamic Boarding School’s English Vocabulary Teaching Model at a Boarding Based Vocational School - Bahrul Walidin; Maslathif Dwi Purnomo; Sholihatul Hamidah Daulay; Ainol Mardhiah (FKIP - Universitas Riau, 2026)
This study examines how a modern Islamic boarding school’s English vocabulary delivery model is used in a boarding based Vocational School. The study aimed to describe the model's use, its benefits, and students' learning processes in vocational education. To investigate this, a qualitative case study was used. Data was collected through class observation, interviews, and documents from SMKS IT Manahilul Irfan in North Aceh, Indonesia. The findings reveal that boarding-school learning practices such as daily vocabulary routines, peer-assisted learning, and the establishment of an English-speaking environment, substantially enhance students’ vocabulary development and communicative confidence. The dormitory context provides continuous language exposure and frequent opportunities for authentic interaction, thereby strengthening both students’ linguistic competence and character formation. Teachers reported that this learning model effectively motivates students and fosters discipline, although challenges remain, such as limited instructional time and varying proficiency levels among learners. Therefore, integrating contemporary boarding-school pedagogical approaches with vocational education offers a comprehensive and contextually relevant framework for vocabulary learning. This integration not only improves students’ English proficiency but also cultivates moral values, self-regulation, and responsibility, thereby contributing to curriculum innovation and offering practical insights for character-oriented language education